2005
DOI: 10.2174/1568011054222300
|View full text |Cite
|
Sign up to set email alerts
|

Triplex-Forming Oligonucleotides as Potential Tools for Modulation of Gene Expression

Abstract: Triplex-forming oligonucleotides (TFOs) bind in the major groove of duplex DNA at polypurine/ polypyrimidine stretches in a sequence-specific manner. The binding specificity of TFOs makes them potential candidates for use in directed genome modification. A number of studies have shown that TFOs can introduce permanent changes in a target sequence by stimulating a cell's inherent repair pathways. TFOs have also been demonstrated to inhibit gene expression providing a possible role for these compounds in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…TFOs bind to specific oligopyrimidine-oligopurine sequences through Hoogsteen hydrogen bonding and are promising tools for genome manipulation (17)(18)(19). By using oligonucleotides with locked nucleic acids (LNAs), DNA-binding affinities in the nanomolar range, which are comparable with those of DNAinteracting proteins, can now be obtained in physiological conditions (20,21).…”
mentioning
confidence: 99%
“…TFOs bind to specific oligopyrimidine-oligopurine sequences through Hoogsteen hydrogen bonding and are promising tools for genome manipulation (17)(18)(19). By using oligonucleotides with locked nucleic acids (LNAs), DNA-binding affinities in the nanomolar range, which are comparable with those of DNAinteracting proteins, can now be obtained in physiological conditions (20,21).…”
mentioning
confidence: 99%
“…By contrast, the binding affinity and specificity of majorgroove DNA triplexes has been studied for decades as a potential means for manipulating gene expression (Sun et al 1996;Barre et al 2000;Diviacco et al 2001;Rogers et al 2005) and as a hypothetical structural form that is believed to occur naturally in DNA regulatory regions (Mirkin and Frank-Kamenetskii 1994;Frank-Kamenetskii and Mirkin 1995). Triple-stranded DNA structures occur so readily because the DNA major groove is wide and accessible for the binding of ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Although triplexes are well characterized in vitro, their biological significance in living organisms is still under discussion (Zain and Sun, 2003). It has been demonstrated that, upon formation, these structures can frequently downregulate (Cooney et al, 1988; Birg et al, 1990; Faria et al, 2000;Faria et al, 2001) and sometimes upregulate (reviewed in Faria and Giovannangeli, 2001) gene expression, a fact which demonstrates their potential in gene control and suggests their use in gene therapy (Wang et al, 1995;Vasquez et al, 2000) (for a review, see Rogers et al, 2005). The structures are also able to impair DNA polymerization (Dayn et al, 1992), and can influence DNA recombination and repair (Faruqi et al, 1996;Wang et al, 1996;Faruqi et al, 2000;Vasquez et al, 2002;Kalish et al, 2005;Raghavan et al, 2005) (for reviews, see Seidman and Glazer, 2003; Chin et al, 2007).…”
mentioning
confidence: 99%